2016
DOI: 10.21767/2172-0479.100077
|View full text |Cite
|
Sign up to set email alerts
|

Raising Awareness about Tuberculosis among Women Living in Rural Communities on the Atlantic Coastline of Nigeria

Abstract: Background: The disease Tuberculosis (TB) is a contagious illness which is rampant in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
3
1
0
Order By: Relevance
“…These findings were similar to those of the previous studies by [11, 21, 24]. The findings also showed that some of the respondents did not know that Drug Resistant TB was not a hereditary disease spread through blood, and transmitted through, witchcraft, and these findings were consistent with those of the previous studies [10, 24, 25]. These results clearly illustrate that a significant proportion of the study participants still lack general knowledge about certain aspects of the disease and this is detrimental to the success of the TB control program.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings were similar to those of the previous studies by [11, 21, 24]. The findings also showed that some of the respondents did not know that Drug Resistant TB was not a hereditary disease spread through blood, and transmitted through, witchcraft, and these findings were consistent with those of the previous studies [10, 24, 25]. These results clearly illustrate that a significant proportion of the study participants still lack general knowledge about certain aspects of the disease and this is detrimental to the success of the TB control program.…”
Section: Discussionsupporting
confidence: 93%
“…Only 48% of the respondents knew that avoiding hugging and shaking hand with Drug Resistant TB infected is not a preventive practice against its transmission. These findings were similar to those of a previous study by [24]. Similar results were found in previous studies by [10, 45] where more than a third of the respondents believed that MDR-TB was transmitted and caused by kissing and touching infected people and therefore avoid kissing and touching the infected persons were regarded as means of preventing infection and its spread.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Iran a large part of the consideration is given by broad doctors in general wellbeing divisions and directed by irresistible sickness subject matter experts and a few by confidential professionals. Obviously for a TB control program to find success, clinicians ought to obtain adequate information and give proper practice fundamental for the administration of TB [4]. The accessible writing shows extensive fluctuation in the avoidance, assessment, and treatment procedures utilized by doctors overall [5].…”
Section: Introductionmentioning
confidence: 99%